2015
DOI: 10.1002/ejoc.201501107
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of the Nucleophilic Reactivities of Cyclic β‐Keto Ester Anions

Abstract: Keywords: Kinetics / Ion pairs / Anions / Enols / Reaction mechanismsKinetics of the reactions of enolate anions derived from acyclic and cyclic β-keto esters with benzhydrylium ions and quinone methides have been determined photometrically in dimethyl sulfoxide solution at 20°C. The reactions follow second-order rate laws: first-order with respect to the electrophile and first-order with respect to the enolate. Reactions conducted in the presence of 18-crown-6 ether and in the presence of variable concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…We obtained these parameters for 264 nucleophiles in different solvents for a total number of 341 data points from Mayr’s data set, which include 41 olefins, , 38 (hetero)­aromatics, ,, 22 Si-enolates (silyl ketene acetals, silyl enol ethers), ,, 35 enamines, ,, 26 ylides, 5 NHCs, 31 anionic C-nucleophiles (carbanions), 67 N-nucleophiles (aliphatic amines, pyridines, imidazoles, etc. ), ,, 27 anionic N-nucleophiles, 41 O-nucleophiles (phenolates and carboxylates), , and 8 S-nucleophiles. , These were chosen over a nucleophilicity range of 35 N units in 7 different solvents (DCM, ACN, THF, acetone, DMF, DMSO, and water).…”
Section: Resultsmentioning
confidence: 99%
“…We obtained these parameters for 264 nucleophiles in different solvents for a total number of 341 data points from Mayr’s data set, which include 41 olefins, , 38 (hetero)­aromatics, ,, 22 Si-enolates (silyl ketene acetals, silyl enol ethers), ,, 35 enamines, ,, 26 ylides, 5 NHCs, 31 anionic C-nucleophiles (carbanions), 67 N-nucleophiles (aliphatic amines, pyridines, imidazoles, etc. ), ,, 27 anionic N-nucleophiles, 41 O-nucleophiles (phenolates and carboxylates), , and 8 S-nucleophiles. , These were chosen over a nucleophilicity range of 35 N units in 7 different solvents (DCM, ACN, THF, acetone, DMF, DMSO, and water).…”
Section: Resultsmentioning
confidence: 99%
“…The next focus is to probe suitable N , O -acetal-based conditions using an intermolecular variant (Scheme ). However, the activated N -lactoyl iminium species in situ generated from 41 under protonic or Lewis acidic conditions severely suffered from either double bond isomerization followed by recapture by methanol to produce 50 or tautomerization to form trans -enamide 51 , and was found to be reluctant to undergo Mannich addition with the lactonic nucleophile (for details, see the Supporting Information of ref ) . To devise a workaround, we became keenly aware of the alcohol exchange phenomenon of N , O -acetals under pyrolytic conditions reported by Ben-Ishai in the 1960s .…”
Section: Resultsmentioning
confidence: 99%
“…Av arietyo fo ther arylsubstituted indanone-based ketoesters were all well tolerated, and gratifyingly the tetralonep roduct 3q could also be obtained in reasonable selectivity.S urprisingly,t he synthesis of the acyclic a-hydroxy-b-ketoester 3r was not possible under our base-free conditions. [25] When carrying out the above described H/D exchange NMR experiment on this startingm aterial (please compare with Figure 1f or starting material 2a), we found that in this specific case no H/D exchange takesp lace under base-free conditions, thus rationalizingt he missingr eactivity under our standard conditions. By adding an inorganic base the reaction proceeds well, but only with low enantioselectivity.…”
Section: Resultsmentioning
confidence: 99%